2020
DOI: 10.1159/000510970
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prognostic Impact of Intracranial Hemorrhage after Endovascular Treatment for Acute Large Vessel Occlusion

Abstract: <b><i>Introduction:</i></b> Endovascular treatment (EVT) is effective against acute cerebral large vessel occlusion (LVO). However, it has been associated with a high incidence of intracranial hemorrhage (ICH). Because the incidence of ICH and prognostic impact of ICH were not scrutinized in general patients, we investigated the impact of ICH after EVT on functional outcome at 90 days in patients with acute LVO. <b><i>Methods:</i></b> RESCUE-Japan Registry 2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…AICH including asymptomatic ICH and SICH has been reported to worsen clinical outcomes. 28,29 Therefore, the increase in AICH after 2 passes should be considered important.…”
Section: Discussionmentioning
confidence: 99%
“…AICH including asymptomatic ICH and SICH has been reported to worsen clinical outcomes. 28,29 Therefore, the increase in AICH after 2 passes should be considered important.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a previous registry study showed that both asymptomatic and symptomatic ICH after EVT in patients with acute LVO were associated with worse functional outcomes. 34 The meta-analysis from HERMES (the Highly Effective Reperfusion evaluated in Multiple Endovascular Stroke Trials) showed a higher rate of symptomatic ICH after EVT in patients with low ASPECTS, but it did not report the association between symptomatic ICH and functional outcomes. 35 MRI with susceptibility-weighted imaging or T2* weighted imaging could provide more accurate qualitative information of cerebral microbleeds, which were reported to increase ICH after EVT.…”
Section: Discussionmentioning
confidence: 99%
“…The timing and causes of death after EVT in routine clinical practice have remained largely unknown. Registry-based studies focusing on hemorrhagic complications, 9 12 space-occupying edema formation 13 15 or infectious complications as pneumonia 16 , 17 have suggested that these are frequent causes of death after EVT, but the relative frequencies of the complications and the timing of their occurrence are unknown. A better understanding of the causes of death after EVT may inform future studies aiming to improve outcomes and increase the chance of survival.…”
Section: Introductionmentioning
confidence: 99%